Mortgaging Europe's periphery - Dorothee Bohle (London School of Economics and Political Science (LSE), European Institute, 2017)
This paper is concerned with the development of housing finance in peripheral European states. Interestingly, the biggest mortgage and housing booms and busts prior to the Global Financial Crisis (GFC) have occurred in these countries, rather than in the core. This is surprising, given the comparatively low level of mortgage debt and the unsophisticated financial sectors in the periphery. The mortgage and housing booms and busts have also made these countries highly vulnerable to the fallout from the GFC, and have often been associated with severe banking and even sovereign debt crises. The paper asks why peripheral countries have been particularly vulnerable to housing and mortgage booms and busts; how these have shaped their exposure to the GFC, and how the GFC has affected peripheral housing finance. Building on literature on housing financialization and varieties of residential capitalism, the paper traces trajectories of housing-induced financialization before and after the GFC in four European peripheral countries: Hungary, Latvia, Ireland and Iceland. The paper argues that their differences notwithstanding, Europe's East and peripheral Northwest have been characterized by high homeownership rates and unsophisticated mortgage markets. The evolving EU framework for free movement of capital and provision of financial services as well as the availability of ample and cheap credit has induced a trajectory of financialization, which has taken two major but not mutually exclusive forms: domestic financial institutions' reliance on funding from wholesale markets, and direct penetration of foreign financial institutions. These two forms of financialization attest to a core-periphery relationship in the recent episode of housing financialization, whose hierarchical character played out in the crisis. Peripheral European countries experienced sudden stops and reversals of capital flows, which badly affected their banking systems. Unable to solve the looming banking crises on their own, they had to turn to creditors to gain access to much needed capital inflows. Different combinations of international conditionality, domestic policy responses and the original level of mortgage debt result in different trajectories in housing finance after the crisis.
Keywords: 330; comparative political economy; international political economy; housing; financialization; peripheral capitalism